Rancang Bangun Sistem E-Voting Pemilihan Ketua Umum IMM Kaizen Surabaya Berbasis WEB - Moch. Ghulam Abrari Binuri; Tining Hariyanti (SinarFe7, 2022)
IMM (Muhammadiyah Student Association) Kaizen is one of the organizations located on the campus of the University of Muhammadiyah Surabaya. So far, the election of candidates for the chairmanship of the IMM kaizen for the new period is still carried out in the conventional way, and direct voting does not utilize information technology. The voting process is carried out by checking the candidates for the chairmanship and then collected and calculated manually. E-Voting is an election system where election data is stored and processed in digital information output. E-Voting can also be interpreted as voting whose implementation process starts from the registration of voters, the implementation of voting, counting votes and sending the results of votes is carried out electronically.Analyzing a running system is one step to determine the direction of action to be planned, system analysis is a stage of current system analysis, which is carried out before the system design process to find out the problems that arise. Based on the results of studies, observations and system design, members are expected to be able to choose the general chairman easily and quickly. This technical reconciliation system can reduce problems with manual systems, including cost efficiency and reduce and create errors.